ACUTE KIDNEY INJURY (AKI) PADA KEHAMILAN - Satriyo Dwi Suryantoro; Djoko Santoso; Sarah Firdausa (Universitas Syiah Kuala, 2021)
Acute Kidney Injury (AKI) in pregnancy remains a cause for fetomaternal morbidity and mortality, particularly in developing countries. Hypertensive complications of pregnancy (preeclampsia/eclampsia, HELLP syndrome) remains the leading cause of AKI in pregnancy. A set of systemic and renal physiological adaptive mechanisms occur during a normal gestation that will cause several changes in laboratory parameters of renal function, electrolytes, fluid and acid – base balance. Diagnosis of AKI in pregnancy is based on the serum creatinine increase and reduction of urine output. Management of AKI in pregnancy requires a multidisciplinary approach between nephrologists and obstetricians for optimizing care for both mother and child. In approaching AKI in pregnant woman, emphasis should be placed on making early and accurate diagnosis to allow prompt intervention and to facilitate recovery from AKI.